1996
DOI: 10.1016/s0022-5223(96)70265-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and long-term results after thymoma resection: A series of 307 patients

Abstract: Three hundred seven cases of patients who underwent operation for thymoma (196 of whom had myasthenia gravis) were analyzed to assess the prognostic values of Masaoka clinical staging, completeness of resection, histologic classification, history of myasthenia gravis, and postoperative radiotherapy. According to the Masaoka staging system, 135 thymomas were stage I, 70 were stage II, 83 were stage III, and 19 were stage IV. According to the Verley and Hollmann histologic classification system, 67 thymomas were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
298
3
39

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 404 publications
(359 citation statements)
references
References 19 publications
(1 reference statement)
19
298
3
39
Order By: Relevance
“…27,51 However, the use of this factor in prognostication has been controversial as some studies have not found an association of survival with myasthenia gravis. 29,52,53 In this current series, types A and AB thymomas had a similar pattern of recurrence/metastasis and thus can be regarded as a single category. Indeed, Suster and Moran 54 have proposed a classification system that groups types A and AB along with types B1 and B2 under a single rubric of 'typical thymoma.'…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…27,51 However, the use of this factor in prognostication has been controversial as some studies have not found an association of survival with myasthenia gravis. 29,52,53 In this current series, types A and AB thymomas had a similar pattern of recurrence/metastasis and thus can be regarded as a single category. Indeed, Suster and Moran 54 have proposed a classification system that groups types A and AB along with types B1 and B2 under a single rubric of 'typical thymoma.'…”
Section: Discussionmentioning
confidence: 54%
“…Although some promote and anticipate a benign clinical course for these tumors, 6,[12][13][14][15][16] others (ourselves included) consider all thymomas as potentially malignant neoplasms. [1][2]10,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Many prior studies have documented malignant behavior in types A and AB thymomas. In our retrospective study of 71 cases of types A and AB thymomas (37 cases with follow-up information available), 18 patients (nine each of types A and AB) developed recurrence and or metastases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations